Implementation of Humanistic Approach in Differentiated Social Studies Learning for Grade V Students of SDN 1 Mesuji Timur - Rasmaita Rasmaita (Jurnal Profesi Pendidikan, 2025)
This study aims to analyze how the humanistic approach is applied in differentiated learning in elementary schools. The study found that there are similarities in concept between the differentiated learning approach and the humanistic approach, both of which emphasize the importance of appreciating the uniqueness of each individual. Conducted at SDN 1 MESUJI TIMUR, this study is a type of qualitative descriptive research with a case study approach. The researcher aims to identify natural patterns that emerge when applying the humanistic approach in differentiated learning. Observations were made on the planning, implementation, and evaluation of learning. Data collection techniques involve diagnostics, observation, performance, and final tests. The subjects of the study consisted of 15 fifth grade students of SDN 1 MESUJI TIMUR, consisting of 8 boys and 7 girls in the 2024/2025 academic year. The findings of the study indicate that the application of the humanistic approach in differentiated learning has a positive impact on creativity and student learning outcomes.